EFFECT OF GELATIN ANTI-TRANSPIRATION IN SOME GROWTH AND YIELD CHARACTERISTICS OF WHEAT UNDER WATER STRESS - A. Abraheem, B. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A Field experiment was carried out in the winter season 2015- 2016 in county Rasheed south of Baghdad, In order to Increasing the efficiency of water use of wheat plant by anti-transpiration manufactured compared with commercial anti-transpiration. Gelatin with two concentration 0.5 and 1.5% and pure gelatin with 1.5%, in the growth and yield of wheat Triticum aestivum L. Then Compared to Commercial anti- transpiration armourax, with water stress levels which is used three levels of water depletion: 40, 60 and 80 of available water. The experiment was designed by using RCBD, with the split plot design with three replications. The results were related negatively between moisture depletion and growth parameters, yield as well as the increasing depletion moisture were caused plummeted vegetative growth parameters, yield and component yield, expected water use. So the surplus of water has been significant in both of treats 60 and 80% compared to 40% depletion of water irrigation, while both of treatments were provided amount of water, will be able to irrigate extra-Land approximately 0.34 and 0.44 hectare for both treats respectively, in addition that, anti-transpirations   were reduced the impacts of water stress in most of growth parameters, yield, water use efficiency and Profitability of irrigation water. This indicates the ability of anti-transpirations (organic) to reduce water stress damages in some of vegetative treats and yield of wheat.